Sarcoma Stem Cells: Do We Know What We Are Looking for?. (9th May 2012) - Trucco, Matteo; Loeb, David
Abstract : Sarcomas represent a heterogeneous group of cancers thought to originate from malignant transformation of mesenchymal cells. There is increasing evidence that many, if not all, sarcomas contain within them tumor-initiating, or "cancer stem, " cells responsible for the initiation, maintenance, and potentially relapse and metastasis of the tumor. Various techniques have been adopted in recent years to identify putative sarcoma stem cell populations. The goal of this paper is to summarize the criteria used to identify a stem cell population, describe the more prominent markers and techniques used to isolate cancer stem cells in sarcomas, and review the evidence for the existence of cancer stem cells in sarcomas.